Laparosocpic “Intraperitoneal Underlay Mesh”-Plus: A Viable Approach for Incisional-Ventral Hernia Repair - Elie Chelala; Brian Jacob (Journal of Abdominal Wall Surgery)
The current Intraperitoneal Underlay Mesh (IPUM), previously referred to as IPOM (onlay), initially faced several challenges due to design and methodological shortcomings, particularly with the use of a bridging technique without defect closure. These limitations contributed to elevated recurrence rates, mesh bulging, seroma formation, and suboptimal abdominal wall function. Although complications such as adhesions, bowel erosion, fistula formation, and mesh migration were rare, they were mostly associated with non-composite or poorly designed meshes and inadequate fixation. These concerns led to growing skepticism regarding intraperitoneal mesh placement and a shift in preference toward retrorectus mesh positioning. Since 2007, the evolution of IPUM+ techniques—where the “+” denotes primary defect closure combined with the use of advanced composite meshes, has led to significantly improved outcomes. Long-term studies, meta-analyses, and randomized trials have demonstrated better functional results, reduced complications, and broader acceptance among surgeons and patients. These advancements have positioned IPUM+ as a reliable and effective option, especially when long-term outcomes of alternative techniques such as eTEP, ventral TAPP, or robotic approaches remain under long term follow up evaluation. IPUM+ continues to serve as a valuable technique for small to moderate or recurrent ventral hernias when performed by experienced surgeons. Future directions should aim to define its role in personalized hernia care, integrating hybrid methods and emerging technologies for complex repairs.